EFFORTS OF BPJS KETENAGAKERJAAN IN SOCIALIZING OF AN OLD-AGE SECURITY PROGRAM TO INFORMAL WORKERS IN THE CITY OF MEDAN - Riana Tambunan (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to determine the efforts BPJS Ketenagakerjaan in socializing the old age security program to informal workers in Medan City and the obstacles faced by Employment BPJS in socializing the old age security program. The research method used is descriptive qualitative. Data collection techniques are observation, interviews, and documentation. The results of this study indicate that the efforts BPJS Ketenagakerjaan in socializing the old age security program to informal workers in the city of Medan have been going well. The obstacles experienced by BPJS Ketenagakerjaan are the lack of public awareness regarding the culture of saving and the importance of the old age security program, the community only considers registering and does not consider this old age security as a necessity. This article contributes as an additional reference that can help BPJS Ketenagakerjaan to find an innovation in socializing the JHT program and the constraints that occur according to the community's perspective.